An Optical Fiber Measurement System for Blade Tip Clearance of Engine - Jia Binghui; He Lei (International Journal of Aerospace Engineering)
The benefits of reducing the tip clearance have been receiving many scholars’ attention all the time, which bring turbine efficiency increasing, emissions reduction, payloads increasing, and mission range abilities extension. In order to gain the blade tip clearance dynamically, a prototype optical fiber measurement system was built and tested based on the rotor test rig. The optical fiber tip clearance measurement system consists of the reflective intensity-modulated optical fiber bundle (sensor), main signal processing unit, high-speed data acquisition card, and a computer. The static performance and dynamic performance experiments were conducted to verify the performance of the system we designed. In addition, the results show that the accuracy of the system is 25 μm or better; the stability of the measurement system was evaluated in room temperature. The clearance measurement range is about 5 mm, and sensitivity of the sensor is 0.0733/mm. Furthermore, the typical tip clearance dynamic measurement experiment results show that the system has good dynamic response characteristics as well. The system will provide a new tool for engine health monitoring or fast active tip clearance control.